Coating containing resin composition as well as preparation method and application of coating
By using coatings containing resin compositions, the problem of insufficient high temperature resistance performance of existing anticorrosion coatings in high temperature environments is solved, efficient protection of the coating is achieved, and the service life of the equipment is extended.
Patent Information
- Application Number
- CN202411937556.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The existing anticorrosion coatings have insufficient high temperature resistance in high-temperature working environments and are prone to aging, resulting in a decrease in acid corrosion resistance and cannot effectively protect the concrete structure of wet desulfurization chimneys.
A coating containing a resin composition is provided. By mixing the resin composition, a curing agent and an auxiliary material, a coating with high bond strength and short surface drying time is formed, and has good high temperature resistance, acid corrosion resistance, urge cooling and heat resistance.
The coating of this coating maintains good bonding strength and corrosion resistance in high temperature environments, extending the service life of the inner wall of the wet desulfurization chimney and avoiding serious corrosion of the equipment.
Smart Images

Figure SMS_5 
Figure SMS_6 
Figure SMS_7
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of resin coatings, and in particular to a coating containing a resin composition, and a preparation method and application thereof. Background Art
[0002] As a thermosetting resin, epoxy resin molecules have excellent adhesion, wear resistance, corrosion resistance and good mechanical properties after curing. At the same time, they have the advantages of excellent processability, stability and low cost. They are one of the most widely used basic resins in polymer materials.
[0003] As the country's environmental protection policies in the power industry continue to increase, coal-fired power generation units must be equipped with wet desulfurization equipment within a certain period of time. The wet desulfurization process is a gas-liquid reaction with a fast reaction speed, high desulfurization efficiency, and safe and reliable production and operation.
[0004] However, the wet flue gas desulfurization device is located at the end of the flue. Since the wet flue gas desulfurization chimney is in a high temperature and acidic corrosive medium environment for a long time, the durability of its concrete structure will be significantly reduced and the equipment will be seriously corrosive. The existing anti-corrosion coating has insufficient high temperature resistance. In a high temperature working environment, the coating ages, causing its acid corrosion resistance to decrease until the coating fails. Summary of the invention
[0005] The purpose of the present application is to solve the above-mentioned technical problems and to provide a coating containing a resin composition, a preparation method and an application thereof. After the coating containing the resin composition is simulated and coated on the inner wall of a wet desulfurization chimney, the obtained coating has good bonding strength, short surface drying time, and good high temperature resistance, acid corrosion resistance, and resistance to rapid cooling and rapid heating; and the coating containing the resin composition is a solvent-free system with a low content of volatile organic compounds (VOCs), and is an environmentally friendly coating.
[0006] The technical solution of this application In a first aspect, the present application provides a coating containing a resin composition, which adopts the following technical solution: A coating containing a resin composition, which is composed of a resin composition, a curing agent and an auxiliary material mixture, wherein the usage of the resin composition, the curing agent and the auxiliary material mixture is calculated by weight ratio, and the resin composition: the curing agent: the auxiliary material mixture is 100:30-50:50-150; The resin composition, calculated by weight, has the following raw material compositions and contents: 5-15 parts of triglycidyl isocyanurate Bisphenol F episulfide resin 25-65 parts 10-50 parts of tetraglycidylamine epoxy resin; The curing agent, calculated by weight, has the following raw material composition and content: Aromatic amine 30-70 parts Alicyclic amine 10-30 parts Aminopropyl cyclotetrasiloxane 5-20 parts 2-4 parts of accelerator; The aromatic amine is a compound of diaminodiphenylmethane and diethyltoluenediamine, and the compounding ratio is calculated by weight, and diaminodiphenylmethane: diethyltoluenediamine is 1:0.1-0.6; The above-mentioned alicyclic amine is 1,3-cyclohexanedimethylamine (1,3-BAC), and other alicyclic amines such as isophoronediamine (IPDA), 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane (DMDC), and 4,4-diaminodicyclohexylmethane (DC) that can be used in the coating field are also suitable for the above-mentioned coating containing the resin composition; The above-mentioned accelerator is triethanolamine, and other accelerators such as 1-methylimidazole and 2,4,6-tris(dimethylaminomethyl)phenol (DMP-30) that can be used in the coating field are also suitable for the above-mentioned coating containing the resin composition; The auxiliary material mixture, calculated by weight, has the following raw material compositions and contents: Silane coupling agent 1-3 parts Rheological additive 0.5-3 parts Wetting and dispersing agent 1-10 parts Glass flakes 50-80 pieces Mica powder 20-50 parts; The above-mentioned silane coupling agent is KH550, and other silane coupling agents such as KH560 and KH570 that can be used in the coating field are also suitable for the above-mentioned coating containing the resin composition; The above-mentioned rheological additive is GARAMITE-1958; The above-mentioned wetting and dispersing agent is BYK-P104S; The particle size of the above-mentioned glass flakes is 1200-1300 mesh; The particle size of the mica powder is 1200-1300 mesh; The resin composition, curing agent and auxiliary material mixture can be stored separately, or the resin composition can be mixed evenly with 10%-50% of the total weight of the auxiliary material mixture, and the curing agent can be mixed evenly with the remaining auxiliary material mixture and then stored separately, and mixed before use.
[0007] By adopting the above technical scheme, the coating containing the resin composition has a bonding strength of 6.1-7.9MPa, a surface drying time of 1.8-3.0h, a heat resistance test pass rate of 90%-99%, an acid corrosion resistance test pass rate of 90%-96%, and a rapid cooling and rapid heating resistance test pass rate of 90%-97%. Therefore, the coating containing the resin composition has good bonding strength, short surface drying time, and good high temperature resistance, acid corrosion resistance, and rapid cooling and rapid heating resistance.
[0008] Furthermore, the coating containing the resin composition has good bonding strength, short surface drying time, and good high temperature resistance, acid corrosion resistance, and resistance to rapid cooling and heating. It solves the technical problems of existing anti-corrosion coatings such as insufficient high temperature resistance and easy aging in high temperature working environments. It has good durability after coating and can play a long-term protective role when used in the concrete structure of the wet desulfurization chimney, further preventing the equipment from being severely corroded.
[0009] Furthermore, the coating containing the resin composition has ultra-low volatile organic compounds (VOCs), and while improving the anti-corrosion performance of the wet desulfurization chimney, it will not cause additional or secondary pollution to the environment, and is an environmentally friendly coating.
[0010] Preferably, in the above-mentioned coating containing the resin composition, the amounts of the resin composition, the curing agent and the auxiliary material mixture, calculated by weight ratio, are 100:40:100 of the resin composition:curing agent:auxiliary material mixture.
[0011] Preferably, the resin composition in the coating containing the resin composition is calculated by weight ratio of triglycidyl isocyanurate: bisphenol F type episulfide resin: tetraglycidylamine type epoxy resin = 1:5:4.
[0012] By adopting the above technical scheme, the coating containing the resin composition has a bonding strength of 7.9MPa, a surface drying time of 2.8h, a heat resistance test pass rate of 99%, an acid corrosion resistance test pass rate of 96%, and a rapid cooling and heating resistance test pass rate of 97%. At the same time, the coating has suitable viscosity, is easy to process, and has good operability.
[0013] In a second aspect, the present application provides a method for preparing a coating containing a resin composition, using the following technical solution: The above-mentioned method for preparing a coating containing a resin composition comprises the following preparation steps: S1: Preparation of excipient mixture (1) Preparation of auxiliary material mixture I: Add mica powder and glass flakes in sequence, control the speed to 30-60r / min and mix evenly to obtain auxiliary material mixture I; (2) Preparation of auxiliary material mixture II: Add silane coupling agent, rheological additive and wetting dispersant in sequence, control the speed to 50-100r / min and mix evenly to obtain auxiliary material mixture II; S2: Preparation of resin composition Add tetraglycidylamine epoxy resin into container I, heat the tetraglycidylamine epoxy resin to 110-130° C., then control the stirring speed to 50-100 r / min, add triglycidyl isocyanurate and stir evenly, then stop heating, add bisphenol F episulfide resin and stir evenly, and cool to room temperature to obtain a resin composition; S3: Preparation of curing agent Add aromatic amine to container II, heat to 100-110°C, control the speed to 50-100r / min and stir until the aromatic amine becomes a uniform liquid, stop heating, then add alicyclic amine, aminopropyl cyclotetrasiloxane and accelerator in sequence under stirring, continue stirring and mixing, and then cool to room temperature to obtain a curing agent; S4: preparing the coating containing the resin composition according to the amount ratio of the resin composition, the curing agent and the auxiliary material mixture; First, add 10%-50% of the total weight of auxiliary material mixture II to the resin composition, and stir evenly at room temperature at a speed of 50-100 r / min, then add 10%-50% of the total weight of auxiliary material mixture I, and stir evenly at a speed of 30-60 r / min to obtain mixture A; Then, the remaining auxiliary material mixture II and auxiliary material mixture I are added to the curing agent in sequence, and stirred evenly at room temperature at a speed of 30-60 r / min to obtain a mixture B; S5: Add the mixture B obtained in S4 into the mixture A, control the rotation speed to 20-50 r / min and stir evenly to obtain a coating containing the resin composition.
[0014] By adopting the above technical scheme, the method for preparing the coating containing the resin composition is simple and easy to operate because simple processes such as mixing are adopted in the preparation process, and therefore it is suitable for large-scale production.
[0015] Furthermore, in the method for preparing a coating containing a resin composition, auxiliary material mixture I and auxiliary material mixture II are added to the resin composition in a certain proportion to obtain mixture A, and the remaining portion is added to a curing agent to obtain mixture B. The viscosity of mixture A and mixture B is controlled to be basically the same, so that mixture A and mixture B are easier to mix evenly, thereby improving the preparation efficiency of the coating containing the resin composition.
[0016] In a third aspect, the application of the coating containing the resin composition obtained above in the inner wall coating of a wet desulfurization chimney adopts the following technical solution: The application of a coating containing a resin composition in the inner wall coating of a wet desulfurization chimney specifically comprises the following steps: The coating containing the resin composition obtained above is applied to the inner wall of the wet desulfurization chimney, and the coating thickness is controlled to be 2-3 mm. The coating is naturally dried after coating.
[0017] By adopting the above technical scheme, the coating containing the resin composition has good bonding strength, short surface drying time, and good high temperature resistance, acid corrosion resistance, and resistance to rapid cooling and rapid heating. It solves the technical problems of existing anti-corrosion coatings such as insufficient high temperature resistance and easy aging in high temperature working environment. The coating has good durability after coating and can play a long-term protective role when used in the concrete structure of the wet desulfurization chimney, further preventing the equipment from being severely corroded.
[0018] Preferably, the coating containing the resin composition obtained above is used in the inner wall coating of a wet desulfurization chimney. During the coating process, coating is performed every 12 hours, and the thickness of each coating is controlled to be 450-550 μm.
[0019] By adopting the above technical scheme, the coating containing the resin composition is coated in multiple layers, which has better high temperature resistance, acid corrosion resistance and rapid cooling and heating resistance than coating once.
[0020] Beneficial technical effects of this application The coating containing a resin composition of the present application is composed of a resin composition, a curing agent and an auxiliary material mixture, does not contain a non-reactive diluent, has a low content of volatile organic compounds (VOCs), and is environmentally friendly.
[0021] The present invention discloses a method for preparing a coating containing a resin composition, which is simple in preparation, convenient in operation, and high in preparation efficiency, and is therefore suitable for large-scale production.
[0022] A coating containing a resin composition of the present application is simulated and coated on the inner wall of a wet desulfurization chimney. The resulting coating can be dry within 3 hours at room temperature. At the same time, it has good bonding strength, high temperature resistance, acid corrosion resistance, and resistance to rapid cooling and heating, and can provide long-term protection for the concrete structure in the wet desulfurization chimney. DETAILED DESCRIPTION
[0023] The present application is further described in detail below in conjunction with embodiments.
[0024] The names, models or specifications of the raw materials used in the examples of this application and the information of the manufacturers or suppliers are shown in the following table: Raw material name Model or specification Manufacturer or supplier Triglycidyl isocyanurate T-4005 Dongguan Long Innovation Materials Technology Co., Ltd. Bisphenol F episulfide resin FP 9900 (EX) Luhe High-tech Materials (Shanghai) Co., Ltd. Tetraglycidylamine type epoxy resin EP 8404 Luhe High-tech Materials (Shanghai) Co., Ltd. Diethyltoluenediamine E100 Jinan Shengda Chemical Co., Ltd. Methylenedianiline DDM Heze Yonghui Composite Materials Co., Ltd. 1,3-Cyclohexanedimethylamine 1,3-BAC Jiangsu Xinsu New Materials Co., Ltd. Aminopropylcyclotetrasiloxane CTS103 Guangzhou Yixin Technology Co., Ltd. Triethanolamine Purity ≥99% Commercially available Silane coupling agent KH550 Xinke Chemical Technology Co., Ltd. Rheology additives GARAMITE-1958 BYK Wetting and dispersing agents BYK-P104S BYK Glass flakes 1200-1300 mesh Commercially available Mica powder 1200-1300 mesh Commercially available The structural formula of the triglycidyl isocyanurate is: ; The structural formula of the bisphenol F type episulfide resin is: , where the degree of polymerization n is 0-1; The structural formula of the tetraglycidylamine type epoxy resin is: ; The structural formula of the aminopropylcyclotetrasiloxane is: .
[0025] In each application example of the present application, the bonding strength (bonding strength with cement mortar), surface drying time, heat resistance (250°C ± 5°C, constant temperature for 1h), acid corrosion resistance (the sample is immersed in 80°C, 40% H2SO4 for 15 days), rapid cooling and rapid heating resistance (the sample is placed at 250°C ± 5°C / 23°C ± 2°C + blowing, each constant temperature for 1h, and cycled 5 times) of the coating containing the resin composition obtained and the qualification judgment are all in accordance with the industry standard DL / T 693-1999 "Acid-resistant and anti-corrosion coating for chimney concrete"; Among them, the samples for heat resistance, acid corrosion resistance and rapid cooling and heating resistance tests have 100 samples for each test item. After each sample is tested, if the coating / sample has no cracks, blistering, or peeling (as shown in Table 1 of DL / T 693-1999 standard), the sample has passed the assessment and is a qualified sample; Among them, the samples for the heat resistance, acid corrosion resistance and rapid cooling and heating resistance tests are coated once (the corresponding coating thickness of one coating is about 2 mm), twice (the corresponding coating thickness of each coating is about 1 mm, and the interval between two coatings is 12 h) and four times (the corresponding coating thickness of each coating is about 500 μm, and the interval between each coating is 12 h) in the sample preparation process of Example 1, and the total coating thickness is 2 mm, and the test samples of the coating containing the resin composition with different coating times of Example 1 are obtained respectively; The sample preparation process of the remaining embodiments and comparative examples is 4 coatings (the coating thickness of each coating is about 500 μm, and the interval between each coating is 12 hours), and the total coating thickness is 2 mm, and test samples of the coating containing the resin composition of different embodiments (the default number of coatings is 4 times) are obtained respectively.
[0026] The equipment models and manufacturer information used in the testing process of this application are as follows: The digital fully automatic pull-off adhesion tester used for the bond strength test is PosiTest AT-A, produced by Defelsko, USA; The high temperature aging test chamber used for heat resistance testing is model LH-225, produced by Nanjing Huanke Testing Equipment Co., Ltd. Example 1
[0027] A coating containing a resin composition, wherein the raw materials used in its preparation consist of a resin composition, a curing agent and a mixture of auxiliary materials; The composition and content (kg) of each raw material used in the preparation of the above-mentioned resin composition, curing agent and auxiliary material mixture are shown in the following table:
[0028] The above-mentioned coating containing a resin composition has the resin composition, curing agent and auxiliary material mixture used in its preparation in an amount calculated by weight of resin composition: curing agent: auxiliary material mixture of 100:40:100.
[0029] The method for preparing the coating containing the resin composition comprises the following preparation steps: S1: Preparation of excipient mixture (1) Preparation of auxiliary material mixture I: Add mica powder and glass flakes in sequence, control the speed to 50r / min and mix evenly to obtain auxiliary material mixture I; (2) Preparation of auxiliary material mixture II: Silane coupling agent (KH550), rheological additive (GARAMITE-1958) and wetting and dispersing agent (BYK-P104S) were added in sequence, and the mixing speed was controlled at 80 r / min to obtain auxiliary material mixture II; S2: Preparation of resin composition Add tetraglycidylamine epoxy resin into container I, heat the tetraglycidylamine epoxy resin to 120° C., then control the stirring speed to 80 r / min, add triglycidyl isocyanurate and stir evenly, then stop heating, add bisphenol F episulfide resin and stir evenly, and then cool to room temperature to obtain a resin composition; S3: Preparation of curing agent Add aromatic amines (diethyltoluenediamine and diethyltoluenediamine) in container II in sequence, heat to 105°C, control the speed to 80r / min and stir for 1.5h to obtain aromatic amine in a uniform liquid, stop heating, and then add alicyclic amine (1,3-cyclohexanedimethylamine), aminopropylcyclotetrasiloxane and accelerator (triethanolamine) in sequence under stirring, continue stirring for 0.8h to mix evenly, and then cool to room temperature to obtain a curing agent; S4: Take 100 kg of resin composition, 40 kg of curing agent and 100 kg of auxiliary material mixture; 50% of the total weight of auxiliary material mixture II, i.e. 2.5 kg of auxiliary material mixture II, was added to 100 kg of the resin composition, and the mixture was stirred at 80 r / min at room temperature, and then 50% of the total weight of auxiliary material mixture I, i.e. 47.5 kg of auxiliary material mixture I, was added, and the mixture was stirred at 50 r / min to obtain mixture A; Then, the remaining auxiliary material mixture II (2.5 kg) and the remaining auxiliary material mixture I (47.5 kg) were added to 40 kg of the curing agent, and the rotation speed was controlled to 50 r / min at room temperature, and the mixture was stirred evenly to obtain a mixture B; S5: Add the mixture B obtained in S4 into the mixture A, control the rotation speed to 30 r / min and stir evenly to obtain a coating containing the resin composition.
[0030] The coating containing the resin composition obtained above was applied to the sample, and the bonding strength, surface drying time, heat resistance, acid corrosion resistance, and rapid cooling and heating resistance were tested respectively, as shown in the following table:
[0031] It can be seen from the data in the above table that the bonding strength and surface drying time of the coating containing the resin composition meet the requirements of DL / T 693-1999 "Acid-resistant anti-corrosion coating for chimney concrete". In addition, after the coating containing the resin composition is applied, the qualified rate of the heat resistance test is 91%-99%, the qualified rate of the acid corrosion test is 90%-96%, and the qualified rate of the rapid cooling and rapid heating test is 90%-97%. In particular, after 4 times of application, the qualified rate of the heat resistance test reaches 99%, the qualified rate of the acid corrosion test reaches 96%, and the qualified rate of the rapid cooling and rapid heating test reaches 97%.
[0032] The above results show that multiple coatings of the coating containing the resin composition have a better effect than a single coating, and can enhance the durability of the coating in the wet desulfurization chimney to extend the service life of the wet desulfurization chimney. Comparative Examples 1-6 of Example 1
[0033] A coating containing a resin composition, the raw material composition and content used in its preparation are the same as those in Example 1 except that the raw material composition and content (kg) in the resin composition are different from those in Example 1, as shown in the following table:
[0034] The preparation method of the coating containing the resin composition is the same as that of Example 1.
[0035] The coatings containing the resin composition obtained in Comparative Examples 1-6 of Example 1 were tested for bonding strength, surface drying time, heat resistance, acid corrosion resistance, and resistance to rapid cooling and rapid heating, and compared with the test data of Example 1 (4 times), as shown in the following table: Test items Example 1 (4 times) Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Bond strength (MPa) 7.9 6.4 6.8 3.3 6.7 5.9 4.5 Surface drying time (h) 2.8 6.8 1.5 2.5 4.5 1.8 4.8 Heat resistance test pass rate (%) 99 80 70 88 82 87 84 Acid corrosion resistance test pass rate (%) 96 76 92 19 78 55 46 Rapid cooling and rapid heating resistance test pass rate (%) 97 87 86 40 86 66 60 It can be seen from the data analysis of Example 1 (4 times) and Comparative Example 1 in the above table that in the coating containing the resin composition, when the raw material components and contents of the curing agent and the auxiliary material mixture remain unchanged and the usage ratio of the resin composition, the curing agent and the auxiliary material mixture is the same, when triglycidyl isocyanurate is used alone in the resin composition, its surface drying time is longer. The reason for this may be that triglycidyl isocyanurate is a solid powder, which easily absorbs moisture in the air and deliquesces. Too high a content of triglycidyl isocyanurate causes the coating containing the resin composition to be unevenly dispersed, thereby affecting the performance of the cured product and the quality of the coating.
[0036] It can be seen from the data analysis of Example 1 (4 times) and Comparative Example 2 in the above table that when bisphenol F episulfide resin is used alone in the resin composition, the qualified rate of its heat resistance performance is low and the cost of bisphenol F episulfide resin is high.
[0037] From the data analysis of Example 1 (4 times) and Comparative Example 3 in the above table, it can be seen that when tetraglycidylamine type epoxy resin is used alone in the resin composition, its bonding strength is relatively low, which is 3.3 MPa, and the pass rate of the acid corrosion resistance test is only 19%, and the pass rate of the rapid cooling and rapid heating resistance test is only 40%.
[0038] It can be seen from the data analysis of Example 1 (4 times) and Comparative Examples 4-6 in the above table that when any two of triglycidyl isocyanurate, bisphenol F type episulfide resin and tetraglycidylamine type epoxy resin are used in combination in the resin composition, the performance effect of the coating containing the obtained resin composition is not as good as the effect when the three are used in combination.
[0039] The above results show that when the resin composition obtained by compounding triglycidyl isocyanurate, bisphenol F type episulfide resin and tetraglycidylamine type epoxy resin is used as one of the raw material components of the coating, the coating containing the resin composition has better comprehensive performance. Comparative Examples 7-10 of Example 1
[0040] A coating containing a resin composition, the raw material components and contents used in its preparation are the same as those in Example 1 except that the raw material composition and content (kg) of the curing agent are different from those in Example 1, as shown in the following table:
[0041] The preparation method of the coating containing the resin composition is the same as that of Example 1.
[0042] The coatings containing the resin composition obtained in Comparative Examples 7-10 of Example 1 above were applied to the test specimens, and the bonding strength, surface drying time, heat resistance, acid corrosion resistance, and rapid cooling and heating resistance were tested respectively, and compared with the test data of Example 1 (4 times), as shown in the following table: Test items Example 1 (4 times) Comparative Example 7 Comparative Example 8 Comparative Example 9 Comparative Example 10 Bond strength (MPa) 7.9 6.6 3.6 1.6 6.7 Surface drying time (h) 2.8 27 1.9 1.2 15 Heat resistance test pass rate (%) 99 96 88 95 96 Acid corrosion resistance test pass rate (%) 96 93 78 92 96 Rapid cooling and rapid heating resistance test pass rate (%) 97 80 71 92 89 It can be seen from the data analysis of Example 1 (4 times) and Comparative Example 7 in the above table that in a coating containing a resin composition, when the raw material components and contents of the resin composition and the auxiliary material mixture remain unchanged, and the usage ratios of the resin composition, the curing agent and the auxiliary material mixture are the same, when only aromatic amines (diethyltoluenediamine) and accelerators (triethanolamine) are used in the curing agent, the surface drying time required for the coating containing the resin composition is longer.
[0043] From the data analysis of Example 1 (4 times) and Comparative Example 8 in the above table, it can be seen that when only alicyclic amine (1,3-cyclohexanedimethylamine) and accelerator (triethanolamine) are used in the curing agent, the bonding strength of the coating containing the resin composition obtained is relatively low, which is 3.6 MPa, and the qualified rate of the heat resistance test is only 88%, the qualified rate of the acid corrosion resistance test is only 78%, and the qualified rate of the rapid cooling and rapid heating resistance test is only 71%, which are all lower than Example 1.
[0044] From the data analysis of Example 1 (4 times) and Comparative Example 9 in the above table, it can be seen that when only aminopropyl cyclotetrasiloxane and accelerator (triethanolamine) are used in the curing agent, the bonding strength is low, only 1.6 MPa.
[0045] From the data analysis of Comparative Examples 7 and 10 in the above table, it can be seen that among the aromatic amine components in the curing agent, when diaminodiphenylmethane and diethyltoluenediamine are used in combination, the surface drying time required for the coating containing the resin composition obtained is shorter than that when diethyltoluenediamine is used alone; and the qualified rate of its acid corrosion resistance is increased from 93% to 96%, and the qualified rate of its rapid cooling and rapid heating resistance is increased from 80% to 89%.
[0046] The above results show that the curing agent component of the coating containing the resin composition uses aromatic amine (diaminodiphenylmethane and diethyltoluenediamine in combination), alicyclic amine (1,3-cyclohexanedimethylamine), and aminopropylcyclotetrasiloxane in combination with an accelerator (triethanolamine) for better effect. Comparative Examples 11-13 of Example 1
[0047] A coating containing a resin composition, the raw material components and contents used in its preparation are the same as those in Example 1 except that the raw material composition and content of the auxiliary material mixture are different from those in Example 1, as shown in the following table:
[0048] The preparation method of the coating containing the resin composition is the same as that of Example 1.
[0049] The coatings containing the resin composition obtained in Comparative Examples 11-13 of Example 1 were applied to the test specimens, and the bonding strength, surface drying time, heat resistance, acid corrosion resistance, and rapid cooling and heating resistance were tested respectively, and compared with the test data of Example 1 (4 times), as shown in the following table: Test items Example 1 (4 times) Comparative Example 11 Comparative Example 12 Comparative Example 13 Bond strength (MPa) 7.9 6.6 6.5 6.9 Surface drying time (h) 2.8 3.0 2.8 2.3 Heat resistance test pass rate (%) 99 97 97 96 Acid corrosion resistance test pass rate (%) 96 88 85 86 Rapid cooling and rapid heating resistance test pass rate (%) 97 91 86 89 From the data of Example 1 (4 times) and Comparative Examples 11-13 in the above table, it can be seen that when the auxiliary material mixture is compounded with glass flakes, mica powder, silane coupling agent (KH550), rheological additive (GARAMITE-1958) and wetting dispersant (BYK-P104S), the coating containing the resin composition obtained has better comprehensive properties such as bonding strength, surface drying time, heat resistance, acid corrosion resistance, and resistance to rapid cooling and rapid heating. Embodiment 2-5
[0050] A coating containing a resin composition, the raw material components and contents used in its preparation are the same as those in Example 1 except that the content (kg) of the resin composition is different from that in Example 1, as shown in the following table:
[0051] The preparation method of the coating containing the resin composition is the same as that of Example 1.
[0052] The coatings containing the resin composition obtained in the above Examples 2-5 were applied to the samples, and the bonding strength, surface drying time, heat resistance, acid corrosion resistance, and rapid cooling and heating resistance were tested respectively, and compared with the test data of Example 1 (4 times), as shown in the following table: Test items Example 1 (4 times) Example 2 Example 3 Example 4 Example 5 Bond strength (MPa) 7.9 7.3 7.0 7.2 7.0 Surface drying time (h) 2.8 2.4 2.1 2.4 2.9 Heat resistance test pass rate (%) 99 94 96 95 97 Acid corrosion resistance test pass rate (%) 96 92 95 93 90 Rapid cooling and rapid heating resistance test pass rate (%) 97 93 94 94 90 Through the data analysis of Example 1 (4 times) and Examples 2-5 in the above table, it can be seen that in the coating containing the resin composition, when the raw material components and contents of the curing agent and the auxiliary material mixture remain unchanged, and the usage ratios of the resin composition, the curing agent and the auxiliary material mixture are the same, when triglycidyl isocyanurate, bisphenol F type episulfide resin and tetraglycidylamine type epoxy resin are compounded in different proportions in the resin composition, the bonding strength after coating is 7.0-7.9MPa, the surface drying time is 2.1-2.9h, the qualified rate of heat resistance test is 94%-99%, the qualified rate of acid corrosion resistance test is 90%-96%, the qualified rate of rapid cooling and rapid heating resistance test is 90%-97%, and the comprehensive performance is good.
[0053] In particular, when the compounding ratio of triglycidyl isocyanurate, bisphenol F type episulfide resin and tetraglycidylamine type epoxy resin in the resin composition is 1:5:4, the coating containing the resin composition after coating has a bonding strength of 7.9MPa, a surface drying time of 2.8h, a heat resistance test pass rate of 99%, an acid corrosion resistance test pass rate of 96%, and a rapid cooling and rapid heating resistance test pass rate of 97%. The coating containing the resin composition has better comprehensive performance. Examples 6-10
[0054] A coating containing a resin composition, the raw material components and contents used in its preparation are the same as those in Example 1 except that the content (kg) of the curing agent is different from that in Example 1, as shown in the following table:
[0055] The preparation method of the coating containing the resin composition is the same as that of Example 1.
[0056] The coatings containing the resin composition obtained in Examples 6-10 were applied to the samples, and the bonding strength, surface drying time, heat resistance, acid corrosion resistance, and rapid cooling and heating resistance were tested respectively, and compared with the test data of Example 1 (4 times), as shown in the following table: Test items Example 1 (4 times) Example 6 Example 7 Example 8 Example 9 Example 10 Bond strength (MPa) 7.9 7.3 7.8 6.4 6.1 6.6 Surface drying time (h) 2.8 1.9 2.7 2.5 2.1 2.9 Heat resistance test pass rate (%) 99 97 98 95 94 97 Acid corrosion resistance test pass rate (%) 96 93 95 92 91 93 Rapid cooling and rapid heating resistance test pass rate (%) 97 96 95 92 91 90 Through the data analysis of Example 1 (4 times) and Examples 6-10 in the above table, it can be seen that in the coating containing the resin composition, when the raw material components and contents of the resin composition and the auxiliary material mixture remain unchanged, and the usage ratios of the resin composition, the curing agent and the auxiliary material mixture are the same, when the compounding ratio of the aromatic amine in the curing agent is 1:0.1-0.6 according to the weight ratio of diaminodiphenylmethane: diethyltoluenediamine, the obtained coating containing the resin composition after coating has a bonding strength of 6.1-7.9MPa, a surface drying time of 1.9-2.9h, a heat resistance test pass rate of 94%-99%, an acid corrosion resistance test pass rate of 91%-96%, and a rapid cooling and rapid heating resistance test pass rate of 90%-97%, and has good comprehensive performance. Examples 11-12
[0057] A coating containing a resin composition, the raw material components and contents used in its preparation are the same as those in Example 1 except that the content (kg) of the curing agent is different from that in Example 1, as shown in the following table:
[0058] The preparation method of the coating containing the resin composition is the same as that of Example 1.
[0059] The coating containing the resin composition obtained in the above Examples 11-12 was applied to the sample, and the bonding strength, surface drying time, heat resistance, acid corrosion resistance, and rapid cooling and heating resistance were tested respectively, as shown in the following table: Test items Embodiment 11 Example 12 Bond strength (MPa) 6.6 7.1 Surface drying time (h) 2.3 3.0 Heat resistance test pass rate (%) 96 98 Acid corrosion resistance test pass rate (%) 91 96 Rapid cooling and rapid heating resistance performance test pass rate (%) 96 92 From the data analysis of the above table, it can be seen that the coating containing the resin composition obtained in Examples 11-12 has a bonding strength of 6.6-7.1 MPa after coating, a surface drying time of 2.3-3.0 h, a heat resistance test pass rate of 96%-98%, an acid corrosion resistance test pass rate of 91%-96%, and a rapid cooling and rapid heating resistance test pass rate of 92%-96%, and has good comprehensive performance. Examples 13-15
[0060] A coating containing a resin composition, the raw material components and contents used in its preparation are the same as those in Example 1 except that the content (kg) of the auxiliary material mixture is different from that in Example 1, as shown in the following table:
[0061] The preparation method of the coating containing the resin composition is the same as that of Example 1.
[0062] The coating containing the resin composition obtained in the above Examples 13-15 was applied to the sample, and the bonding strength, surface drying time, heat resistance, acid corrosion resistance, and rapid cooling and heating resistance were tested respectively, as shown in the following table: Test items Embodiment 13 Embodiment 14 Embodiment 15 Bond strength (MPa) 6.8 7.0 7.5 Surface drying time (h) 2.7 2.6 2.7 Heat resistance test pass rate (%) 92 95 95 Acid corrosion resistance test pass rate (%) 90 92 92 Rapid cooling and rapid heating resistance test pass rate (%) 91 90 92 From the data analysis of the above table, it can be seen that the coatings containing the resin composition obtained in Examples 13-15 have a bonding strength of 6.8-7.5 MPa after coating, a surface drying time of 2.6-2.7 h, a heat resistance test pass rate of 92%-95%, an acid corrosion resistance test pass rate of 90%-92%, and a rapid cooling and rapid heating resistance test pass rate of 90%-92%, and the comprehensive performance is good. Examples 16-19
[0063] A resin composition, except that the amount (kg) of the raw materials used in its preparation is different from that in Example 1, the rest is the same as that in Example 1, as shown in the following table: Dosage (kg) Example 1 Example 16 Embodiment 17 Embodiment 18 Embodiment 19 Resin composition 100 100 100 100 100 Curing agent 40 30 50 40 40 Excipient mixture 100 100 100 50 150 The preparation method of the coating containing the resin composition is the same as that of Example 1.
[0064] The coatings containing the resin compositions obtained in Examples 16-19 were applied to the samples, and the bonding strength, surface drying time, heat resistance, acid corrosion resistance, and rapid cooling and heating resistance were tested respectively, and compared with the test data of Example 1 (4 times), as shown in the following table: Test items Example 1 (4 times) Example 16 Embodiment 17 Embodiment 18 Embodiment 19 Bond strength (MPa) 7.9 6.5 6.8 7.1 6.6 Surface drying time (h) 2.8 3.0 1.8 2.9 1.9 Heat resistance test pass rate (%) 99 90 92 95 99 Acid corrosion resistance test pass rate (%) 96 92 90 90 91 Rapid cooling and rapid heating resistance performance test pass rate (%) 97 90 94 91 93 Through the data analysis of Example 1 (4 times) and Examples 16-17 in the above table, it can be seen that in the coating containing the resin composition, when the raw material components and contents of the resin composition, curing agent and auxiliary material mixture remain unchanged, the amounts of the resin composition, curing agent and auxiliary material mixture, calculated by weight ratio, are 100:30-50:100 for the resin composition: curing agent: auxiliary material mixture. The obtained coating containing the resin composition has a bonding strength of 6.5-7.9 MPa after 4 coatings, a surface drying time of 1.8-3.0 h, a heat resistance test pass rate of 90%-99%, an acid corrosion resistance test pass rate of 90%-96%, and a rapid cooling and rapid heating resistance test pass rate of 90%-97%, and has good comprehensive performance.
[0065] By comparing the data of Example 1 (4 times) and Examples 18-19 in the above table, it can be seen that in the coating containing the resin composition, when the raw material components and contents of the resin composition, curing agent and auxiliary material mixture remain unchanged, the amounts of the resin composition, curing agent and auxiliary material mixture, calculated by weight ratio, are 100:40:50-150 for the resin composition:curing agent:auxiliary material mixture. The obtained coating containing the resin composition has a bonding strength of 6.6-7.9 MPa, a surface drying time of 1.9-2.9 h, a heat resistance test pass rate of 95%-99%, an acid corrosion resistance test pass rate of 90%-96%, and a rapid cooling and rapid heating resistance test pass rate of 91%-97% after 4 coatings, and has good comprehensive performance.
[0066] In particular, in Example 1, when the amount of the resin composition, the curing agent and the auxiliary material mixture is calculated by weight ratio, the resin composition: the curing agent: the auxiliary material mixture is 100:40:100, and the comprehensive performance of the coating containing the resin composition is better. After 4 coatings, the bonding strength is 7.9MPa, the surface drying time is 2.8h, the heat resistance test pass rate is 99%, the acid corrosion resistance test pass rate is 96%, and the rapid cooling and rapid heating resistance test pass rate is 97%. Embodiment 20
[0067] A coating containing a resin composition, wherein the raw material composition and content used in its preparation are the same as those in Example 1.
[0068] The method for preparing the coating containing the resin composition comprises the following preparation steps: S1: Preparation of excipient mixture (1) Preparation of auxiliary material mixture I: Add mica powder and glass flakes in sequence, control the speed to 30r / min and mix evenly to obtain auxiliary material mixture I; (2) Preparation of auxiliary material mixture II: Silane coupling agent (KH550), rheological additive (GARAMITE-1958) and wetting dispersant (BYK-P104S) were added in sequence, and the mixing speed was controlled at 50 r / min to obtain auxiliary material mixture II; S2: Preparation of resin composition Add tetraglycidylamine epoxy resin into container I, heat the tetraglycidylamine epoxy resin to 130° C., then control the stirring speed to 50 r / min, add triglycidyl isocyanurate and stir evenly, then stop heating, add bisphenol F episulfide resin and stir evenly, and then cool to room temperature to obtain a resin composition; S3: Preparation of curing agent Add aromatic amines (diethyltoluenediamine and diethyltoluenediamine) in container II in sequence, heat to 100°C, control the speed to 50r / min and stir for 2h to obtain aromatic amine in a uniform liquid, stop heating, and then add alicyclic amine (1,3-cyclohexanedimethylamine), aminopropylcyclotetrasiloxane and accelerator (triethanolamine) in sequence under stirring, continue stirring for 1h to mix evenly, and then cool to room temperature to obtain a curing agent; S4: Take 100 kg of resin composition, 40 kg of curing agent and 100 kg of auxiliary material mixture; 50% of the total weight of auxiliary material mixture II, i.e., 2.5 kg of auxiliary material mixture II, was added to 100 kg of the resin composition, and the mixture was stirred at a speed of 50 r / min at room temperature, and then 50% of the total weight of auxiliary material mixture I, i.e., 47.5 kg of auxiliary material mixture I, was added, and the mixture was stirred at a speed of 30 r / min to obtain mixture A; Then, the remaining auxiliary material mixture II (2.5 kg) and the remaining auxiliary material mixture I (47.5 kg) were added to 40 kg of the curing agent, and the rotation speed was controlled at 30 r / min at room temperature and stirred evenly to obtain a mixture B; S5: Add the mixture B obtained in S4 into the mixture A, control the rotation speed to 20 r / min and stir evenly to obtain a coating containing the resin composition. Embodiment 21
[0069] A coating containing a resin composition, wherein the raw material composition and content used in its preparation are the same as those in Example 1.
[0070] The method for preparing the coating containing the resin composition comprises the following preparation steps: S1: Preparation of excipient mixture (1) Preparation of auxiliary material mixture I: Add mica powder and glass flakes in sequence, control the speed to 60r / min and mix evenly to obtain auxiliary material mixture I; (2) Preparation of auxiliary material mixture II: Silane coupling agent (KH550), rheological additive (GARAMITE-1958) and wetting and dispersing agent (BYK-P104S) were added in sequence, and the mixing speed was controlled at 100 r / min to obtain auxiliary material mixture II; S2: Preparation of resin composition Add tetraglycidylamine epoxy resin into container I, heat the tetraglycidylamine epoxy resin to 110° C., then control the stirring speed to 100 r / min, add triglycidyl isocyanurate and stir evenly, then stop heating, add bisphenol F episulfide resin and stir evenly, and then cool to room temperature to obtain a resin composition; S3: Preparation of curing agent Add aromatic amines (diethyltoluenediamine and diethyltoluenediamine) in container II in sequence, heat to 110°C, control the speed to 100r / min and stir for 1h to obtain aromatic amine in a uniform liquid, stop heating, and then add alicyclic amine (1,3-cyclohexanedimethylamine), aminopropylcyclotetrasiloxane and accelerator (triethanolamine) in sequence under stirring, continue stirring for 0.5h to mix evenly, and then cool to room temperature to obtain a curing agent; S4: Take 100 kg of resin composition, 40 kg of curing agent and 100 kg of auxiliary material mixture; 50% of the total weight of auxiliary material mixture II, i.e. 2.5 kg of auxiliary material mixture II, was added to 100 kg of the resin composition, and the mixture was stirred at room temperature at a speed of 100 r / min, and then 50% of the total weight of auxiliary material mixture I, i.e. 47.5 kg of auxiliary material mixture I, was added, and the mixture was stirred at a speed of 60 r / min to obtain mixture A; Then, the remaining auxiliary material mixture II (2.5 kg) and the remaining auxiliary material mixture I (47.5 kg) were added to 40 kg of the curing agent, and the rotation speed was controlled to 60 r / min at room temperature, and the mixture was stirred evenly to obtain a mixture B; S5: Add the mixture B obtained in S4 into the mixture A, control the rotation speed to 50 r / min and stir evenly to obtain a coating containing the resin composition.
[0071] The coating containing the resin composition obtained in the above Examples 20-21 was applied to the sample, and the bonding strength, surface drying time, heat resistance, acid corrosion resistance, and rapid cooling and heating resistance were tested respectively, as shown in the following table: Test items Embodiment 20 Embodiment 21 Bond strength (MPa) 7.6 7.8 Surface drying time (h) 2.9 2.8 Heat resistance test pass rate (%) 98 96 Acid corrosion resistance test pass rate (%) 90 91 Rapid cooling and rapid heating resistance test pass rate (%) 93 91 By comparing the data in the above table, it can be seen that the coating containing the resin composition obtained in Examples 20-21 has a bonding strength of 7.6-7.8 MPa after coating, a surface drying time of 2.8-2.9 h, a heat resistance test pass rate of 96%-98%, an acid corrosion resistance test pass rate of 90%-91%, and a rapid cooling and rapid heating resistance test pass rate of 91%-93%, and has good comprehensive performance.
[0072] To sum up, the coating containing a resin composition of the present application has good bonding strength, short surface drying time, and good high temperature resistance, acid corrosion resistance, and resistance to rapid cooling and rapid heating, which solves the technical problems of existing anti-corrosion coatings such as insufficient high temperature resistance and easy aging in high temperature working environment.
[0073] The specific embodiments of the present application are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. A resin composition, characterized in that Calculated by weight, the raw material composition and content used in its preparation are as follows: 5-15 parts of triglycidyl isocyanurate Bisphenol F episulfide resin 25-65 parts 10-50 parts of tetraglycidylamine type epoxy resin.
2. A resin composition according to claim 1, characterized in that, In the resin composition, calculated by weight ratio, triglycidyl isocyanurate: bisphenol F type episulfide resin: tetraglycidylamine type epoxy resin = 1:5:
4.
3. A coating containing the resin composition according to claim 1 or 2, characterized in that: The raw materials used in its preparation are composed of a resin composition, a curing agent and a mixture of auxiliary materials, calculated by weight ratio. The amounts of the resin composition, the curing agent and the mixture of auxiliary materials are calculated by weight ratio. The resin composition is: The curing agent: auxiliary material mixture is 100:30-50:50-150; The curing agent, calculated by weight, has the following raw material composition and content: Aromatic amine 30-70 parts Alicyclic amine 10-30 parts Aminopropyl cyclotetrasiloxane 5-20 parts 2-4 parts of accelerator; The aromatic amine is a compound of diaminodiphenylmethane and diethyltoluenediamine, and the compounding ratio is calculated by weight, and the diaminodiphenylmethane: diethyltoluenediamine is 1:0.1-0.6; The above-mentioned alicyclic amine is 1,3-cyclohexanedimethylamine; The above-mentioned accelerator is triethanolamine; The auxiliary material mixture, calculated by weight, has the following raw material compositions and contents: Silane coupling agent 1-3 parts Rheological additive 0.5-3 parts Wetting and dispersing agent 1-10 parts Glass flakes 50-80 pieces Mica powder 20-50 parts; Wherein, the above-mentioned silane coupling agent is KH550; The above-mentioned rheological additive is GARAMITE-1958; The above-mentioned wetting and dispersing agent is BYK-P104S; The particle size of the above-mentioned glass flakes is 1200-1300 mesh; The particle size of the mica powder is 1200-1300 mesh; The resin composition, curing agent and auxiliary material mixture can be stored separately, or the resin composition can be mixed evenly with 10%-50% of the total weight of the auxiliary material mixture, and the curing agent can be mixed evenly with the remaining auxiliary material mixture and then stored separately, and mixed before use.
4. A coating containing a resin composition as claimed in claim 3, characterized in that: The amounts of the resin composition, curing agent and auxiliary material mixture are calculated by weight ratio, and the resin composition is: The curing agent: auxiliary material mixture is 100:40:
100.
5. The method for preparing a coating containing a resin composition according to claim 3, characterized in that: The method comprises the following preparation steps: S1: Preparation of excipient mixture (1) Preparation of auxiliary material mixture I: Add mica powder and glass flakes in sequence, control the speed to 30-60r / min and mix evenly to obtain auxiliary material mixture I; (2) Preparation of auxiliary material mixture II: Add silane coupling agent, rheological additive and wetting dispersant in sequence, control the speed to 50-100r / min and mix evenly to obtain auxiliary material mixture II; S2: Preparation of resin composition Add tetraglycidylamine epoxy resin into container I, heat the tetraglycidylamine epoxy resin to 110-130° C., then control the stirring speed to 50-100 r / min, add triglycidyl isocyanurate and stir evenly, then stop heating, add bisphenol F episulfide resin and stir evenly, and cool to room temperature to obtain a resin composition; S3: Preparation of curing agent Add aromatic amine to container II, heat to 100-110°C, control the speed to 50-100r / min and stir until the aromatic amine becomes a uniform liquid, stop heating, then add alicyclic amine, aminopropyl cyclotetrasiloxane and accelerator in sequence under stirring, continue stirring and mixing, and then cool to room temperature to obtain a curing agent; S4: preparing the resin composition, curing agent and auxiliary material mixture according to the dosage ratio of the coating containing the resin composition; First, add 10%-50% of the total weight of auxiliary material mixture II to the resin composition, and stir evenly at room temperature at a speed of 50-100 r / min, then add 10%-50% of the total weight of auxiliary material mixture I, and stir evenly at a speed of 30-60 r / min to obtain mixture A; Then, the remaining auxiliary material mixture II and auxiliary material mixture I are added to the curing agent in sequence, and stirred evenly at room temperature at a speed of 30-60 r / min to obtain a mixture B; S5: Add the mixture B obtained in S4 into the mixture A, control the rotation speed to 20-50 r / min and stir evenly to obtain a coating containing the resin composition.
6. Use of a coating containing a resin composition as claimed in claim 3 in a coating on the inner wall of a wet desulfurization chimney.
7. Use of a coating containing a resin composition as claimed in claim 6 in a coating on the inner wall of a wet desulfurization chimney, characterized in that: The coating thickness of the coating containing the resin composition on the surface of the wet desulfurization chimney is 2-3 mm.
8. Use of a coating containing a resin composition as claimed in claim 7 in a coating on the inner wall of a wet desulfurization chimney, characterized in that: During the coating process, coating was performed every 12 hours, and the coating thickness was controlled at 450-550 μm each time.
Citation Information
Patent Citations
Thermosetting epoxy resin composition and applications thereof
CN105237949A
Light-sensitive ink and preparation method and application thereof
CN107177231A
Underfill material and preparation method and application thereof
CN114057995A
Cited By
Polymer composite material for circulating water pump and preparation method thereof
CN121825371A